Forecasting Financial Valuation Comparing ARIMA and Prophet - Tchoudi, William; Sergeenko, Grigory (My University, 2022)
In this study, we limit the forecasting period to one year since the same method is applicable to more than one year. The reason for that is the only five-year historic data we have for Discount Cash Flow (DCF) and six years for Price Earning (P/E) and Price to Sale (P/S) valuation. We use a time series approach for comparison, so we use the last given year, which is 2018, for comparison with the predicted value based on all previous years. So, in this study, we compare the predicted 2018 year Using ARIMA and Prophet Methods with the real 2018 year. Some steps were taken to make forecasting and rebuild time series and apply forecasting methodologies. The errors between real data and the forecasted data for both methods shown almost similar results.
Keywords: ARIMA; Discount Cash Flow; forecast; Price Earning; Price to Sale; Prophet